Mapping Suicide Trends in South India: A Secondary Data Analysis of NCRB Reports with Predictive Modelling and Policy Recommendations - Shristi Aich; Neha Vishe; Megha Sharma; Loitongbam Jaya Devi; Riddhi Sanyal (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Suicide presents an increasingly signi𿿿cant challenge to the healthof the Indian population, and patterns of methods and modes of self-harm are changing. During the past few years, the southern states have continued registering one of the highest suicide rates. The growing prevalence of methods that are fatal and the advent of family related suicides are an indication of changing social, psychological and economical strains. Such patterns are crucial in creating responsive and preventive approaches to mental health. Objectives: The objective of the study is to𿿿nd out the trends of suicide in𿿿ve uth Indian states and predict the future trends in order to enable regional planning. It also touches on demographic trends and discrepancies set by gender on the cause basis. Methods: Of𿿿cial NCRB data on suicide over ten years were combined ad aluated. Long-term developments and predictions of the future rates were made with forecasting methods. Regional and gender-related trends were evaluated on the basis of the causes reported and demography available. Results: The results of analysis show that suicide rates continue to increase in the majority of the states in the region. Disparities were noted in the contributing factors between the male and female populations and economic stressors were more common among males and interpersonal or domestic factors were common among women. Conclusion: The results indicate that the need early intervention, area-speci𿿿c mental health care and area-speci𿿿c awareness efforts should be an essential aspect of attempting to prevent the predicted increase in the suicides in South India.